English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

6(x-3)-4(x+1)

a.2x-22
b.2x-14
c.2x-2

4(5x-6)-4(2x+1)
a.12x-5
b.12x-20
c.12x-28

simplify when its possible
10x^2-y+x^2
help with this one definitely i keep getting partial credit.

2007-07-17 14:14:57 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

6(x-3)-4(x+1)=
6x-18-4x-4=
6x-4x-18-4=
2x-22=
x=11

4(5x-6) -4(2x+1)=
4(5x-6)=4(2x+1)
20x-24=8x+4=
12x=28 0r 12x-28
x=28/12



11x^2=y

2007-07-17 14:31:23 · answer #1 · answered by Linda S 5 · 0 0

6(x-3)-4(x+1)=6x-18-4x-4=2x-22. ANS.option a)
4(5x-6)-4(2x+1)=20x-24-8x-4=12x-28option c).ANS.
10x^2-y+x^2=11x^2-y.ANS.

2007-07-17 21:23:33 · answer #2 · answered by Anonymous · 0 1

6x-18-4x-4 (Take it from here)

20x-24-8x-4 Finish it


11x^2-y

2007-07-17 21:17:39 · answer #3 · answered by leo 6 · 0 1

1.a
2.c
3.11x^2-y

2007-07-17 21:18:32 · answer #4 · answered by 037 G 6 · 0 1

fedest.com, questions and answers